A Life To Look Beyond Pristine Nature. Anthropogenic climate change in Attenborough’s Netflix documentaries - Cappi, Valentina (Green Narratives, Ecology and Sustainability in Contemporary Television - Exploring Narrative Ecosystems, 2025)
Documentaries represent a primary conduit through which people encounter information about climate change. A peculiar position is held by nature documentaries, which have been criticized for showing pristine nature without discussing the ongoing eco-climate crisis. This chapter examines as case studies Netflix docuseries Our Planet (2019) and film David Attenborough: A Life on Our Planet (2020), produced in partnership with WWF with the explicit aim of raising awareness of the effects of human action on the planet and of climate change. In light of a review of the issues facing climate change communication and the recommendations identified by scientific research to address them, this study explores how the interaction between specific imagery and language assigns meaning and helps to visualize causes, consequences and solutions to climate change within the two documentaries. T he framing and deductive content analysis show that both products leverage the credibility of Sir David Attenborough and impactful visuals to engage audiences. However, Our Planet omits to thematize climate change causes and solutions, while resulting in the alienation of human presence from its environment. Instead, by adopting diverse stylistic registers, the f ilm succeeds in providing a more interconnected and comprehensive narrative of anthropogenic climate change, showing its social implications and existing mitigation strategies, thus emerging as a more accurate and powerful tool for fostering public awareness.